Lobbying and Negotiation Techniques to Enhance Business Communication Skills through Virtual Reality Training: A Preliminary Study - Juliana, Ari; Shabrina Nurqamarani, Adisthy; Windyaningrum, Rachmawati (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2023)
Lobbying and negotiation skills are some of the required skills to succeed in business and social life. Conventional universities may develop their students’ skills through real-life scenarios while this could be challenging for open and distance universities which students are scattered around the world. Virtual Reality is an alternative technology that allows students to experience real-life scenarios in a simulated environment. This research aims to develop website-based Virtual Reality training to enhance learning in the business communication subject, with a specific focus on lobbying and negotiation techniques in distance education. This research adopts the Borg & Gall Research & Development (R&D) Method for educational research. This paper focuses on the preliminary stage which gathered the data required to construct a high-quality mood board and flowchart aligned with stakeholder needs to produce high-quality virtual reality training to enhance negotiation skills. Primary data is gathered through Focus Group Discussions involving students, tutors, and business communication practitioners. Additionally, secondary data is derived from extensive literature and document reviews, including relevant studies and documents. The result shows that informants are passionate about the idea of using virtual reality to enhance negotiation skills. Options of background, gender, and situation settings as well as interchangeable roleplay are preferred in boosting the motivation and enhancing the practical knowledge of negotiation skills.